Archeologia a tutto campo - Manacorda, Daniele (Reti Medievali Rivista, 2018)
Andrea Augenti’s manual was conceived and written for university students who attend courses on Medieval archaeology. Its organic structure, its overall vision of the relationship between archaeology and history, its conceptual and methodological openings make this book a recommended read for all those who want to understand the current approaches to medieval archaeology in Italy.